Solid electrolyte film and preparation method thereof, diaphragm-free solid-state battery, solid-state battery and mechanical device
Through the method of configuring the precursor liquid in two steps, a solid electrolyte film with high ionic conductivity, excellent mechanical strength and thermal stability was prepared, which solved the problems of low ionic conductivity and insufficient mechanical strength of solid polymer electrolytes in the prior art at room temperature, and achieved efficient improvement of battery performance.
Patent Information
- Application Number
- CN202411352999.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-05-02
AI Technical Summary
The existing solid polymer electrolytes have low ionic conductivity at room temperature, making it difficult to meet the requirements of room temperature cycling and high-magnification operation of batteries. At the same time, the mechanical strength of the polymer is low and it is difficult to resist the puncture of lithium dendrites.
Using a two-step method of configuring the precursor liquid, the lithium salt, the ionic liquid and the crosslinking agent are first mixed and modified to form a modified active component, and then mixed with the polymer monomer and the initiator to form an interpenetrating network of the crosslinking agent and the polymer monomer, and a solid electrolyte film with high ionic conductivity, excellent mechanical strength and thermal stability are prepared.
It has achieved high lithium ion conduction capability, excellent mechanical strength and stability. The solid-state battery prepared with this solid electrolyte film has high ion conductivity, can replace the separator, prepare a separator-free battery, and improve the battery cycle life and safety.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a solid-state electrolyte film and a preparation method thereof, a diaphragm-free solid-state battery, a solid-state battery and a mechanical device. Background Art
[0002] Traditional lithium-ion batteries use liquid electrolytes and separators, which seriously affect the high-temperature performance and safety of the battery, and the use of separators inevitably affects the energy density of the battery. In order to improve the energy density and safety of lithium-ion batteries, solid electrolyte membranes can be used to replace separators and liquid electrolytes.
[0003] Solid polymer electrolytes have attracted wide attention due to their good flexibility, processability, interfacial compatibility and non-flammability. However, the ionic conductivity of solid polymer electrolytes is generally low at room temperature, which makes it difficult to meet the requirements of room temperature cycling and high-rate operation of batteries. In addition, the mechanical strength of the polymer itself is low and it is difficult to resist the penetration of lithium dendrites. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide a solid electrolyte film and a preparation method thereof, a diaphragm-free solid-state battery, a solid-state battery and a mechanical device.
[0005] In a first aspect of the present invention, the present invention provides a method for preparing a solid electrolyte film. According to an embodiment of the present invention, the method comprises: (1) mixing and modifying a lithium salt, an ionic liquid and a cross-linking agent to obtain a modified active component; (2) mixing the modified active component, a polymer monomer and an initiator to obtain a precursor solution, wherein the polymer monomer includes at least one of a boron-containing monomer, a sulfate monomer, a carbonate monomer, an amide monomer, an ether monomer and a fluorine-containing monomer; (3) Applying the precursor solution to a substrate for polymerization to obtain a solid electrolyte film.
[0006] According to the method for preparing a solid electrolyte film according to the above embodiment of the present invention, first, a lithium salt, an ionic liquid and a cross-linking agent are mixed and modified to obtain a modified active component. The ionic liquid and the lithium salt are first combined, and the anion and cation structure can be regulated to achieve high ionic conductivity, a wide electrochemical stability window, stable interface properties and other properties. Subsequently, the ionic liquid is cross-linked with the cross-linking agent. The cross-linking agent contains a rich structure, and segments with different chemical structures can be introduced by cross-linking to achieve a three-dimensional cross-linked polymer network structure. The three-dimensional cross-linked polymer network structure can first improve the mechanical properties of the ionic liquid and the ability to inhibit the growth of lithium dendrites; secondly, there are a large number of spatial positions in the three-dimensional network structure, which can improve the absorption capacity of the ionic liquid; finally, the strong interaction between the cross-linked polymer network and the ionic liquid reduces the solvation barrier of lithium ions, which is beneficial to lithium ion transmission and uniform deposition.
[0007] Then, the modified active component, polymer monomer and initiator are mixed to obtain a precursor solution, wherein the polymer monomer includes at least one of a boron-containing monomer, a sulfate monomer, a carbonate monomer, an amide monomer, an ether monomer and a fluorine-containing monomer. The modified active component is first obtained by step (1), and then the precursor solution is obtained by step (2). The precursor solution configured in two steps can realize the ion coordination structure in a directional manner and improve the ion conductivity. Finally, the precursor solution is applied to the substrate for polymerization. Under the action of the initiator and certain polymerization conditions, the polymer monomer is polymerized, and the polymer monomer and the cross-linking agent also undergo a certain degree of polymerization cross-linking to form an interpenetrating network of the cross-linking agent and the polymer monomer, thereby making the solid electrolyte film have higher strength and thermal stability.
[0008] Therefore, the solid electrolyte film has high lithium ion conductivity, excellent mechanical strength and stability. The solid-state battery prepared using the solid electrolyte film has high ion conductivity, can replace the diaphragm, prepare diaphragm-free batteries, and improve battery cycle life and safety. The method and process are suitable for diaphragm-free battery production, the raw material cost is controllable, and batch preparation of diaphragm-free batteries can be achieved.
[0009] In addition, the method for preparing a solid electrolyte film according to the above embodiment of the present invention also has the following technical features: In some embodiments of the present invention, in step (1), the mass ratio of the lithium salt, the ionic liquid and the cross-linking agent is (4-20): (75-95): (1-5).
[0010] In some embodiments of the present invention, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium difluorophosphate.
[0011] In some embodiments of the present invention, the ionic liquid includes at least one of an imidazole ionic liquid, a quaternary ammonium ionic liquid, a quaternary phosphonium ionic liquid, a pyrrolidine ionic liquid and a piperidine ionic liquid.
[0012] In some embodiments of the present invention, the crosslinking agent includes tetraethyl orthosilicate, methyl orthosilicate, trimethoxysilane, polycarbodiimide, ethylene glycol dimethacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, tetraethylene glycol dimethacrylate, tetraethylene glycol diacrylate, 1,3-propylene glycol dimethacrylate, N,N'-methylene diacrylate, At least one of N,N'-1,4-phenylene diacrylamide, trimethoxypropane trimethacrylate, 1,2-propylene glycol dimethacrylate, 1,3-propylene glycol diacrylate, 1,2-propylene glycol diacrylate, 1,4-butylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,4-butylene glycol diacrylate, 1,3-butylene glycol diacrylate, pentaerythritol diacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate.
[0013] In some embodiments of the present invention, the imidazolium ionic liquid is obtained by neutralizing an alkyl imidazole and an acid, the cation of the imidazolium ionic liquid includes 1-methylimidazole, and the anion of the imidazolium ionic liquid includes at least one of chlorine, tetrafluoroboric acid, hydrogen sulfate, dihydrogen phosphate, trifluoromethanesulfonic acid and trifluoroacetic acid.
[0014] In some embodiments of the present invention, the cation of the quaternary ammonium ionic liquid includes at least one of tetraethylammonium, tetrabutylammonium, alkyltriethylammonium, and alkyltributylammonium, and the anion of the quaternary ammonium ionic liquid includes at least one of chlorine, bromine, tetrafluoroboric acid, hexafluorophosphoric acid, and bistrifluoromethanesulfonimide.
[0015] In some embodiments of the present invention, the cation of the quaternary phosphonium ionic liquid includes alkyl tributyl phosphonium, and the anion of the quaternary phosphonium ionic liquid includes at least one of bromine, tetrafluoroboric acid and bistrifluoromethanesulfonimide.
[0016] In some embodiments of the present invention, the cation of the pyrrolidine-based ionic liquid includes N-alkylpyrrolidine, and the anion of the pyrrolidine-based ionic liquid includes at least one of bromine, tetrafluoroboric acid, hexafluorophosphoric acid and bistrifluoromethanesulfonimide.
[0017] In some embodiments of the present invention, the cation of the piperidine-based ionic liquid includes N-alkylpiperidine, and the anion of the piperidine-based ionic liquid includes at least one of bromine, tetrafluoroboric acid, hexafluorophosphoric acid, and bistrifluoromethanesulfonimide.
[0018] In some embodiments of the present invention, in step (2), the mass ratio of the modified active component, the polymer monomer and the initiator is (59~98.9):(1~40):(0.1~1).
[0019] In some embodiments of the present invention, the initiator includes at least one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), azobisisovaleronitrile (AMBN), dimethyl azobisisobutyrate (AIBME), azoisobutylcyanamide (CABN), diisopropyl azodicarboxylate (DIAD), azobiscyclohexylcarbonitrile (ACCN), benzoyl peroxide (BPO), di(2-ethylhexyl) peroxydicarbonate (EHP), tert-butyl perbenzoate (TBPB), methyl ethyl ketone peroxide (MEKP), mercaptobenzene, thiolates, and alkyl mercaptans.
[0020] In some embodiments of the present invention, the polymer monomer includes at least one of a boron-containing monomer and an amide monomer.
[0021] In some embodiments of the present invention, the boron-containing monomer includes at least one of cyclic borazine, borosilazane, carborane, boron phenolic acid, cyclic borate, allyloxyboron, allylboronic acid pinacol ester, poly(ethylene glycol) methyl methacrylate (B-PEGMA) containing cyclic borazine, tetramethoxyboro lithium, boron dipyrromethylethylene, boron difluorohydrazine, azobenzene boron complex, tri(4-vinylbenzene)borane, triarylborane, diarylborane, boron diketonate, tetraphenylborate, tetrakis(4-chloromethyl-2,3,5,6-tetrafluorophenyl)borate lithium, bis(fluoroallyl)malonate lithium borate, bismaleate lithium borate, (bisphenol AF borate) lithium salt, (4,4′-dihydroxydiphenylsulfone borate) lithium salt and bis(allylmalonate) lithium borate.
[0022] In some embodiments of the present invention, the sulfate monomer includes at least one of 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane, 4-ethylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane, bis((2,2-dioxo-1,3,2-dioxathiapentane-4-yl)methyl) sulfate, monoethyl sulfate, dibutyl sulfate, diisopropyl sulfate, diethyl sulfate, 1,3-propylene glycol cyclic sulfate, bis(trimethylsilyl) sulfate and S-phenylpyrazine-2-carbon sulfate.
[0023] In some embodiments of the present invention, the carbonate monomer includes at least one of isosorbide bis(alkyl carbonate), trimethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate and butylene carbonate.
[0024] In some embodiments of the present invention, the amide monomer includes at least one of N-vinylcaprolactam, acrylamide, methacrylamide, N-methylacrylamide, isopropyl acrylamide, N-ethylacrylamide, isobutoxymethylacrylamide, N-hydroxymethylacrylamide, diacetone acrylamide, N-hydroxyethylacrylamide, N-hydroxypropyl acrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide.
[0025] In some embodiments of the present invention, the ether monomer includes at least one of 1,4-dioxane, ethylene glycol dimethyl ether, glycidyl methyl ether, 1,3-dioxolane, ethylene glycol methyl ether glycidyl ether, ethylene glycol dimethyl ether, 1,3,5-trioxane, diethylene glycol methyl ether glycidyl ether, 1,3-dioxane and 1,4-dioxane.
[0026] In some embodiments of the present invention, the fluorine-containing monomer includes at least one of hexafluoropropylene, hexafluorobutyl acrylate, tetrafluoroethylene, hexafluorobutyl methacrylate, vinyl bis(trifluoromethyl) phosphate, trifluoroethyl methacrylate, allyl bis(2,2,2-trifluoroethyl) phosphate, dodecafluoroheptyl methacrylate, allyl bis(trifluoromethyl) phosphate, 2,2,2-trifluoropropylene diphosphate, dodecafluoroheptyl acrylate, nonadecafluoro acrylate, vinyl bis(2,2,2-trifluoroethyl) phosphate and perfluorobutyl ethyl methacrylate.
[0027] In some embodiments of the present invention, an inorganic material is further added to the system of step (2) and mixed to obtain a precursor solution, wherein the inorganic material comprises at least one of an inorganic solid electrolyte and an inorganic ceramic.
[0028] In some embodiments of the present invention, based on the total mass of the precursor solution, the mass of the inorganic material accounts for 70% to 95%.
[0029] In some embodiments of the present invention, the inorganic solid electrolyte includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a nitride solid electrolyte, a boride solid electrolyte, and a hydride solid electrolyte.
[0030] In some embodiments of the present invention, the inorganic ceramic includes at least one of metal oxides, nitrides, carbides, borides and fluorides.
[0031] In a second aspect of the present invention, a solid electrolyte film is provided. According to an embodiment of the present invention, the solid electrolyte film is prepared by the above method.
[0032] In a third aspect of the present invention, a diaphragm-free solid-state battery is provided. According to an embodiment of the present invention, the diaphragm-free solid-state battery comprises the above-mentioned solid electrolyte film.
[0033] In a fourth aspect of the present invention, a solid-state battery is provided. According to an embodiment of the present invention, the battery comprises the above-mentioned solid-state electrolyte film.
[0034] In a fifth aspect of the present invention, the present invention provides a mechanical device. According to an embodiment of the present invention, the mechanical device includes the above-mentioned membrane-free solid-state battery or the above-mentioned solid-state battery.
[0035] The present invention has at least the following technical effects: The two-step method of preparing the precursor solution is adopted. The ionic liquid and the lithium salt are first combined to realize the ion coordination structure in a directional manner, and the anion and cation structure is regulated to realize the high ionic conductivity, wide electrochemical stability window, stable interface properties and other properties. Then the modified active component is mixed with the polymer monomer and the initiator to form an interpenetrating network of the crosslinker and the polymer monomer, which has higher strength and thermal stability. The precursor solution has low viscosity and good fluidity, and can fully infiltrate the pores between the solid electrolyte and the pole piece and the gap between the active materials in the pole piece, construct the ion transmission path in the pole piece and improve the interface ion transmission kinetics. Then the monomer is converted into a polymer through polymerization, and the ionic liquid is bound in the polymer network, which further improves the safety of the battery. DETAILED DESCRIPTION
[0036] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0037] In a first aspect of the present invention, the present invention provides a method for preparing a solid electrolyte film. According to an embodiment of the present invention, the method comprises: S100: Mixing and modifying lithium salt, ionic liquid and crosslinker
[0038] In this step, the lithium salt, ionic liquid and cross-linking agent are mixed and modified to obtain the modified active component. The ionic liquid and the lithium salt are first combined, which can regulate the anion and cation structure to achieve high ionic conductivity, wide electrochemical stability window, stable interface properties and other properties. The ionic liquid is then cross-linked with the cross-linking agent. The cross-linking agent contains a rich structure. Through cross-linking, segments with different chemical structures can be introduced to achieve a three-dimensional cross-linked polymer network structure. The three-dimensional cross-linked polymer network structure can first improve the mechanical properties of the ionic liquid and the ability to inhibit the growth of lithium dendrites; secondly, there are a large number of spatial positions in the three-dimensional network structure, which can improve the absorption capacity of the ionic liquid; finally, the strong interaction between the cross-linked polymer network and the ionic liquid reduces the solvation barrier of lithium ions, which is beneficial to lithium ion transmission and uniform deposition. It should be noted that the mixed modification can be performed at room temperature.
[0039] According to an embodiment of the present invention, the lithium salt includes but is not limited to at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium difluorophosphate.
[0040] According to an embodiment of the present invention, the crosslinking agent includes but is not limited to ethyl orthosilicate, methyl orthosilicate, trimethoxysilane, polycarbodiimide, ethylene glycol dimethacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, tetraethylene glycol dimethacrylate, tetraethylene glycol diacrylate, 1,3-propylene glycol dimethacrylate, N,N'-methylene diacrylate, At least one of N,N'-1,4-phenylene diacrylamide, trimethoxypropane trimethacrylate, 1,2-propylene glycol dimethacrylate, 1,3-propylene glycol diacrylate, 1,2-propylene glycol diacrylate, 1,4-butylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,4-butylene glycol diacrylate, 1,3-butylene glycol diacrylate, pentaerythritol diacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate.
[0041] According to an embodiment of the present invention, the mass ratio of lithium salt, ionic liquid and cross-linking agent is (4-20): (75-95): (1-5). The inventors found that by controlling the mass ratio of lithium salt, ionic liquid and cross-linking agent within the above range, the ionic liquid has a higher ionic conductivity and a wide electrochemical window while still having a certain mechanical strength.
[0042] According to an embodiment of the present invention, the ionic liquid includes at least one of an imidazole ionic liquid, a quaternary ammonium ionic liquid, a quaternary phosphonium ionic liquid, a pyrrolidine ionic liquid and a piperidine ionic liquid.
[0043] According to an embodiment of the present invention, the imidazole ionic liquid is obtained by neutralizing an alkyl imidazole and an acid, the cation of the imidazole ionic liquid includes 1-methylimidazole, and the anion of the imidazole ionic liquid includes at least one of chlorine, tetrafluoroboric acid, hydrogen sulfate, dihydrogen phosphate, trifluoromethanesulfonic acid and trifluoroacetic acid.
[0044] According to an embodiment of the present invention, the cation of the quaternary ammonium ionic liquid includes at least one of tetraethylammonium, tetrabutylammonium, alkyltriethylammonium (the alkyl group includes ethyl, butyl, hexyl or octyl), and alkyltributylammonium (the alkyl group includes ethyl, butyl, hexyl or octyl), and the anion of the quaternary ammonium ionic liquid includes at least one of chlorine, bromine, tetrafluoroboric acid, hexafluorophosphoric acid and bistrifluoromethanesulfonimide.
[0045] According to an embodiment of the present invention, the cation of the quaternary phosphonium ionic liquid includes alkyl tributyl phosphonium (the alkyl group includes ethyl, butyl, hexyl or octyl), and the anion of the quaternary phosphonium ionic liquid includes at least one of bromine, tetrafluoroboric acid and bistrifluoromethanesulfonimide.
[0046] According to an embodiment of the present invention, the cation of the pyrrolidine-based ionic liquid includes N-methylpyrrolidine (the alkyl group includes ethyl, propyl, butyl, hexyl or octyl), and the anion of the pyrrolidine-based ionic liquid includes at least one of bromine, tetrafluoroboric acid, hexafluorophosphoric acid and bistrifluoromethanesulfonimide.
[0047] According to an embodiment of the present invention, the cation of the piperidine-based ionic liquid includes N-alkylpiperidine (the alkyl group includes ethyl, propyl, butyl, hexyl or octyl), and the anion of the piperidine-based ionic liquid includes at least one of bromine, tetrafluoroboric acid, hexafluorophosphoric acid and bistrifluoromethanesulfonimide.
[0048] S200: Mixing the modified active component, polymer monomer and initiator.
[0049] In this step, the modified active component, the polymer monomer and the initiator are mixed to obtain a precursor solution, and the polymer monomer includes at least one of a boron-containing monomer, a sulfate monomer, a carbonate monomer, an amide monomer, an ether monomer, and a fluorine-containing monomer. The inventor found that the boron-containing monomer is polymerized to form a polymer, and the boron atom acts as a Lewis acid center to cooperate with the lithium salt anion, inhibits the migration of anions, and improves the dissociation of cation-anion pairs, thereby improving the ionic conductivity and the number of lithium ion migrations, and has good high-temperature thermal stability. At the same time, the boron-containing polymer can promote the formation of a stable solid electrolyte interface on the electrode surface, inhibit the formation of space charge, thereby inducing a uniform distribution of lithium ions, and then promoting the uniform deposition of lithium ions. The fluorine-containing monomer is polymerized to form a polymer, and the fluorine atom has a strong electronegativity and bond energy, so it has excellent chemical stability and can withstand the erosion of acid and alkali solvents and decomposition under high voltage. The amide monomer is polymerized to form a polymer, and the polymer has a higher decomposition temperature, thereby improving the safety of the battery cell. The modified active components are first obtained through S100, and then the precursor solution is obtained through S200. The precursor solution configured in two steps can directionally realize the ion coordination structure, improve the ion conductivity, and form an interpenetrating network of cross-linking agents and polymer monomers, so that the solid electrolyte film has higher strength and thermal stability.
[0050] It should be noted that the initiator is a conventional material in the art, and those skilled in the art can select it according to actual conditions. For example, the initiator includes but is not limited to at least one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), azobisisovaleronitrile (AMBN), dimethyl azobisisobutyrate (AIBME), azoisobutylcyanamide (CABN), diisopropyl azodicarboxylate (DIAD), azobiscyclohexylcarbonitrile (ACCN), benzoyl peroxide (BPO), di(2-ethylhexyl) peroxydicarbonate (EHP), tert-butyl perbenzoate (TBPB), methyl ethyl ketone peroxide (MEKP), mercaptobenzene, thiolates and alkyl mercaptans.
[0051] According to an embodiment of the present invention, the mass ratio of the modified active component, the polymer monomer and the initiator is (59-98.9): (1-40): (0.1-1). The inventors found that by controlling the mass ratio of the modified active component, the polymer monomer and the initiator within the above range, the solid electrolyte membrane prepared after polymerization has a high ionic conductivity and a wide electrochemical window while having a certain mechanical strength.
[0052] Preferably, the polymer monomer includes at least one of a boron-containing monomer and an amide monomer. The inventors found that, compared with other polymer monomers, the boron atom acts as a Lewis acid center to cooperate with the lithium salt anion, inhibits the migration of anions, and improves the dissociation of cation-anion pairs, thereby improving the ionic conductivity and the number of lithium ion migrations, and has good high-temperature thermal stability. At the same time, the boron-containing polymer can promote the formation of a stable solid electrolyte interface on the electrode surface, inhibit the formation of space charge, thereby inducing a uniform distribution of lithium ions, and then promoting uniform deposition of lithium ions.
[0053] According to an embodiment of the present invention, the boron-containing monomer includes cyclic borazine, borosilazane, carborane, boron phenolic formaldehyde, cyclic borate, allyloxy boron, allyl boric acid pinacol ester, poly (ethylene glycol) methyl methacrylate (B-PEGMA) containing cyclic borazine, tetramethoxy boron lithium, boron dipyrromethylethylene, boron difluorohydrazine, azobenzene boron complex, tri (4-vinylbenzene) borane, triaryl borane, diaryl borane, boron diketonate, tetraphenyl borate, tetrakis (4-chloromethyl-2,3,5,6-tetrafluorophenyl) lithium borate, bis (fluoroallyl) malonate lithium borate, bis maleate lithium borate, (bisphenol AF boric acid) lithium salt, (4,4'-dihydroxydiphenylsulfone boric acid) lithium salt and bis (allyl malonate) lithium borate at least one.
[0054] According to an embodiment of the present invention, the sulfate monomer includes at least one of 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane, 4-ethylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane, bis((2,2-dioxo-1,3,2-dioxathiapentane-4-yl)methyl)sulfate, monoethyl sulfate, dibutyl sulfate, diisopropyl sulfate, diethyl sulfate, 1,3-propylene glycol cyclic sulfate, bis(trimethylsilyl) sulfate and S-phenylpyrazine-2-carbon sulfate.
[0055] According to an embodiment of the present invention, the carbonate monomer includes at least one of isosorbide bis(alkyl carbonate), trimethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate and butylene carbonate.
[0056] According to an embodiment of the present invention, the amide monomer includes at least one of N-vinylcaprolactam, acrylamide, methacrylamide, N-methylacrylamide, isopropyl acrylamide, N-ethylacrylamide, isobutoxymethylacrylamide, N-hydroxymethylacrylamide, diacetone acrylamide, N-hydroxyethylacrylamide, N-hydroxypropyl acrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide.
[0057] According to an embodiment of the present invention, the ether monomer includes at least one of 1,4-dioxane, ethylene glycol dimethyl ether, glycidyl methyl ether, 1,3-dioxolane, ethylene glycol methyl ether glycidyl ether, 1,3,5-trioxane, diethylene glycol methyl ether glycidyl ether, 1,3-dioxane and 1,4-dioxane.
[0058] According to an embodiment of the present invention, the fluorine-containing monomer includes at least one of hexafluoropropylene, hexafluorobutyl acrylate, tetrafluoroethylene, hexafluorobutyl methacrylate, vinyl bis(trifluoromethyl) phosphate, trifluoroethyl methacrylate, allyl bis(2,2,2-trifluoroethyl) phosphate, dodecafluoroheptyl methacrylate, allyl bis(trifluoromethyl) phosphate, 2,2,2-trifluoropropylene diphosphate, dodecafluoroheptyl acrylate, nonadecafluoro acrylate, vinyl bis(2,2,2-trifluoroethyl) phosphate and perfluorobutyl ethyl methacrylate.
[0059] According to an embodiment of the present invention, an inorganic material is further added to the S200 system and mixed to obtain a precursor solution, and the inorganic material includes at least one of an inorganic solid electrolyte and an inorganic ceramic.
[0060] According to an embodiment of the present invention, based on the total mass of the above-mentioned precursor solution, the mass proportion of the inorganic material is 70% to 95%. By controlling the mass proportion of the inorganic material within the above-mentioned range, the electrolyte membrane has better thermal stability and higher mechanical strength to resist the puncture of lithium dendrites.
[0061] According to an embodiment of the present invention, the inorganic solid electrolyte includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a nitride solid electrolyte, a boride solid electrolyte, and a hydride solid electrolyte.
[0062] As an example, the oxide solid electrolyte includes, but is not limited to, one or more combinations of lithium lanthanum zirconium oxide (LLZO), niobium-doped lithium lanthanum zirconium oxide (LLZNO), tantalum-doped lithium lanthanum zirconium oxide (LLZTO), niobium-tantalum dual-doped lithium lanthanum zirconium oxide (LLZNTO), lithium lanthanum titanium oxide (LLTO), lithium aluminum titanium phosphate (LATP), yttrium titanium phosphate (LYTP), lithium aluminum germanium phosphate (LAGP), and lithium aluminum oxide (LiAlO2).
[0063] As an example, the sulfide solid electrolyte includes, but is not limited to, one or more combinations of lithium germanium phosphosulfide (LGPS), lithium phosphosulfur chloride (LPSCl), lithium thiophosphate (LPS), and glassy sulfides (Li2S-P2S5, Li2S-SiS2, Li2S-B2S3).
[0064] As an example, the halide solid electrolyte includes, but is not limited to, Li3OCl, LiI, Li5ZnI4, Li3OCl 1-x Br x (where 0 < x < 1), Li2XCl4 (X includes Cd and / or Mg), Li2X′I4 (X′ includes Cd and / or Zn), LiMCl5X′′ (M includes one or more of La, Ta, Nb; X′′ includes any one of O, Cl, F, OH), Li 3-x Zr x M′ 1-x Cl6 (M′ includes one or more of Y, Er, Yb, Ho, Lu, 0 ≤ x ≤ 1), or a combination of one or more thereof.
[0065] As an example, the nitride solid electrolyte includes, but is not limited to, one or more combinations of LiPON, Li3N, Li7PN4, LiSi2N3.
[0066] As an example, the boride solid electrolyte includes, but is not limited to, one or more combinations of Li2B4O7, Li2O - B2O3 - P2O5, Li 6+2x [B 10 S 18 S x or a combination of one or more thereof.
[0067] As an example, the hydride solid electrolyte includes, but is not limited to, one or more combinations of Li3AlH6, LiBH4, LiNH2, Li2NH, LiBH4 - LiNH2, LiBH4 - LiX (X = Cl, Br, I).
[0068] According to an embodiment of the present invention, the inorganic ceramic includes at least one of metal oxides, nitrides, carbides, borides, and fluorides.
[0069] As an example, the metal oxide includes, but is not limited to, at least one of alumina, titanium dioxide, zirconium dioxide, and magnesium oxide.
[0070] As an example, the nitride includes, but is not limited to, at least one of silicon nitride, titanium nitride, aluminum nitride, boron nitride, magnesium nitride, and zirconium nitride.
[0071] As an example, the carbide includes at least one of silicon carbide and boron carbide.
[0072] As an example, the boride includes, but is not limited to, at least one of silicon boride, vanadium boride, magnesium boride, and titanium boride.
[0073] As an example, the fluoride includes, but is not limited to, at least one of lithium fluoride, silver fluoride, lanthanum fluoride, copper fluoride, and silver ammine fluoride.
[0074] S300: Apply the precursor solution to the substrate for polymerization
[0075] In this step, the precursor liquid is applied to the substrate for polymerization. Under the action of the initiator and under certain polymerization conditions, the polymer monomers are polymerized to improve the safety performance of the system. The polymer monomers and the cross-linking agent also undergo a certain degree of polymerization and cross-linking to form an interpenetrating network of the cross-linking agent and the polymer monomers, thereby making the solid electrolyte film have higher strength and thermal stability. It should be noted that the application method is a conventional method in the art, such as coating or spraying.
[0076] According to an embodiment of the present invention, the polymerization includes photopolymerization or thermal polymerization.
[0077] As an example, the light source for photopolymerization includes ultraviolet light and visible light, and the polymerization time is 1 min to 60 min.
[0078] As an example, the heating temperature of thermal polymerization is 30° C. to 120° C., and the heating time is 1 to 80 hours.
[0079] According to an embodiment of the present invention, the substrate includes a pole piece (positive pole piece or negative pole piece), a base film, etc. For example, the precursor solution can be applied to the positive pole piece or the negative pole piece for polymerization, that is, to form a pole piece-solid electrolyte film assembly.
[0080] The base film is a conventional material in the art, for example, the base film includes polyethylene terephthalate (PET), ethylene terephthalate, polybutylene terephthalate, polyethylene (PE), polypropylene (PP), poly-1-butene, polyisobutylene, polybutadiene, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, cellulose, polyvinyl alcohol, polymethyl methacrylate, polyurethane, polycarbonate, polysulfate, aluminum oxide film, polyimide nonwoven film, polyaryl sulfone nonwoven film, silicone oil release film, non-silicon release film, fluorine release film or glass fiber. Further, the thickness of the base film is 1 μm~50 μm, preferably 2 μm~20 μm.
[0081] Preferably, the substrate is a positive electrode sheet or a negative electrode sheet. Applying the precursor solution to the positive electrode sheet or the negative electrode sheet and drying it can increase the contact area between the solid electrolyte layer and the sheet, reduce the interface impedance between the solid electrolyte layer and the sheet, and the formed positive electrode sheet-solid electrolyte film assembly and negative electrode sheet-solid electrolyte film assembly have excellent ionic conductivity.
[0082] In the second aspect of the present invention, the present invention provides a solid electrolyte film. According to an embodiment of the present invention, the solid electrolyte film is prepared by the above method. As a result, the solid electrolyte film has high lithium ion conductivity, excellent mechanical strength and stability. It should be noted that the features and advantages described above for the method for preparing the solid electrolyte film are also applicable to the solid electrolyte film, and will not be repeated here.
[0083] According to an embodiment of the present invention, the thickness of the solid electrolyte film is 10um~20um. When the thickness of the solid electrolyte film is too low, lithium dendrites are easy to puncture and cause battery short circuit. When the thickness of the solid electrolyte film is too high, the increase in ion transmission distance will affect the rate performance of the battery. Therefore, the thickness of the biomass solid electrolyte film of the present application is controlled within the above range, and the battery has higher safety and rate performance.
[0084] In the third aspect of the present invention, the present invention proposes a membrane-free solid-state battery. According to an embodiment of the present invention, the membrane-free solid-state battery includes the above-mentioned solid electrolyte film. As a result, the membrane-free solid-state battery has high ionic conductivity, long cycle life and high safety. It should be noted that the features and advantages described above for the solid electrolyte film and its preparation method are also applicable to the membrane-free solid-state battery, and will not be repeated here.
[0085] In a fourth aspect of the present invention, the present invention provides a solid-state battery. According to an embodiment of the present invention, the battery includes the above-mentioned solid electrolyte film. As a result, the solid-state battery has high ionic conductivity, long cycle life and high safety. It should be noted that the features and advantages described above for the solid electrolyte film and its preparation method are also applicable to the membrane-free solid-state battery, which will not be repeated here.
[0086] According to an embodiment of the present invention, a solid-state battery includes a positive electrode sheet, a solid electrolyte film and a negative electrode sheet.
[0087] As an example, the main material of the positive electrode plate includes but is not limited to one or more combinations of nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and lithium vanadium phosphate; the main material of the negative electrode plate includes but is not limited to one or more combinations of graphite, graphene, carbon nanotubes, silicon-based alloys, silicon-oxygen negative electrodes, silicon-carbon negative electrodes, lithium metal, lithium alloy negative electrodes, lithium titanium oxides, transition metal oxides, and transition metal sulfides.
[0088] In the fifth aspect of the present invention, the present invention proposes a mechanical device. According to an embodiment of the present invention, the mechanical device includes the above-mentioned diaphragm-free solid-state battery or the above-mentioned solid-state battery. As a result, the mechanical device has a long range and service life. It should be noted that the features and advantages described above for the diaphragm-free solid-state and solid-state batteries are also applicable to the mechanical device and will not be repeated here.
[0089] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0090] Example 1
[0091] S1, mixing and modifying lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), pyrrolidine ionic liquid (Pyr13TFSI) and pentaerythritol triacrylate to obtain a modified active component, wherein the mass ratio of the three is 15:82:3; S2, mixing the modified active component, allyl boric acid pinacol ester and azobisisobutyronitrile (AIBN) to obtain a precursor solution, wherein the mass ratio of the three is 70.8:29.1:0.1; S3, coating the precursor solution on PET, polymerizing in a vacuum oven at 80° C. for 12 h to obtain a solid electrolyte film.
[0092] Example 2
[0093] Different from Example 1, the polymer monomer in Example S2 is boron dipyrromethylethylene.
[0094] Example 3
[0095] Different from Example 1, the polymer monomer in Example S2 is triarylborane.
[0096] Example 4
[0097] Different from Example 1, the polymer monomer in S2 in this example is N-methyl acrylamide.
[0098] Example 5
[0099] Different from Example 1, the polymer monomer in Example S2 is diacetone acrylamide.
[0100] Example 6
[0101] Different from Example 1, the polymer monomer in Example S2 is acrylamide.
[0102] Example 7
[0103] Different from Example 1, the polymer monomer in Example S2 is vinylene carbonate.
[0104] Example 8
[0105] Different from Example 1, the polymer monomer in Example S2 is propylene carbonate.
[0106] Example 9
[0107] Different from Example 1, the polymer monomer in Example S2 is 1,3-dioxolane.
[0108] Example 10
[0109] Different from Example 1, the polymer monomer in Example S2 is ethylene glycol dimethyl ether.
[0110] Embodiment 11
[0111] Different from Example 1, the polymer monomer in Example S2 is monoethyl sulfate.
[0112] Example 12
[0113] Different from Example 1, the polymer monomer in Example S2 is 4-ethylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane.
[0114] Embodiment 13
[0115] Different from Example 1, the polymer monomer in Example S2 is tetrafluoroethylene.
[0116] Embodiment 14
[0117] Different from Example 1, the polymer monomer in Example S2 is perfluorobutyl ethyl methacrylate.
[0118] Embodiment 15
[0119] Different from Example 1, the mass ratio of the lithium salt, the ionic liquid and the cross-linking agent in this example is 20:79:1.
[0120] Example 16
[0121] Different from Example 1, the mass ratio of lithium salt, ionic liquid and cross-linking agent in this example is 10:85:5.
[0122] Embodiment 17
[0123] Different from Example 1, the mass ratio of the modified active component, the polymer monomer and the initiator in this example is 62.7:37.2:0.1.
[0124] Embodiment 18
[0125] Different from Example 1, the mass ratio of the modified active component, the polymer monomer and the initiator in this example is 90.2:9.7:0.1.
[0126] Comparative Example 1
[0127] Different from Example 1, in this example, no ionic liquid and cross-linking agent are added in step S1.
[0128] Comparative Example 2
[0129] Different from Example 1, no polymer monomer is added in step S2 in this example.
[0130] Comparative Example 3
[0131] Different from Example 1, in this example, lithium salt, ionic liquid, cross-linking agent, polymer monomer and initiator are directly mixed to prepare the film.
[0132] The battery performance of the embodiment and the comparative example was tested as follows: (1) Ionic conductivity test method
[0133] A stainless steel-solid electrolyte-stainless steel symmetric battery was assembled and the battery was subjected to electrochemical impedance spectroscopy with a frequency range of 0.1 Hz-7 MHz and a test amplitude of 10 mV.
[0134] (2) Cyclic performance test
[0135] Assembly of solid-state batteries: 1) Positive electrode: The mass ratio of lithium nickel cobalt manganese oxide, PVDF and conductive carbon black is 96:2:2.
[0136] 2) Use lithium metal negative electrode as the negative electrode.
[0137] 3) Stack the positive electrode sheet, solid electrolyte and negative electrode sheet in sequence and assemble them into a solid-state battery
[0138] 4) The battery was tested using the Xinwei battery performance test system with a voltage range of 2.7V-4.3V and a charge and discharge condition of 1C cycle at room temperature. The corresponding capacity retention rate was calculated after 100 cycles.
[0139] (3) Tensile strength test method
[0140] The solid electrolyte was cut into strips of 8 cm × 2 cm and the tensile strength was tested using a tensile testing machine at a tensile rate of 20 mm / min.
[0141] (4) CCD test: Assemble lithium metal symmetric battery and test at 0.1 mA cm-2 The current was used as the starting current for constant current charge and discharge for 1 h, and then 0.1 mA cm -2 Continue constant current charging and discharging as the current increases, and record the maximum critical current of the corresponding battery when a short circuit occurs.
[0142] The battery performance test results of the embodiments and comparative examples are shown in Table 1.
[0143] Table 1
[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a solid electrolyte film, characterized in that: include: (1) mixing and modifying a lithium salt, an ionic liquid and a cross-linking agent to obtain a modified active component; (2) mixing the modified active component, a polymer monomer and an initiator to obtain a precursor solution, wherein the polymer monomer includes at least one of a boron-containing monomer, a sulfate monomer, a carbonate monomer, an amide monomer, an ether monomer and a fluorine-containing monomer; (3) Applying the precursor solution to a substrate for polymerization to obtain a solid electrolyte film.
2. The method according to claim 1, characterized in that: In step (1), the mass ratio of the lithium salt, the ionic liquid and the cross-linking agent is (4-20): (75-95): (1-5); and / or, the lithium salt comprises at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium difluorophosphate; And / or, the ionic liquid includes at least one of an imidazole ionic liquid, a quaternary ammonium ionic liquid, a quaternary phosphonium ionic liquid, a pyrrolidine ionic liquid and a piperidine ionic liquid; And / or, the crosslinking agent includes tetraethyl orthosilicate, methyl orthosilicate, trimethoxysilane, polycarbodiimide, ethylene glycol dimethacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, tetraethylene glycol dimethacrylate, tetraethylene glycol diacrylate, 1,3-propylene glycol dimethacrylate, N,N'-methylenediacrylamide, N,N' -1,4-phenylene diacrylamide, trimethoxypropane trimethacrylate, 1,2-propylene glycol dimethacrylate, 1,3-propylene glycol diacrylate, 1,2-propylene glycol diacrylate, 1,4-butylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,4-butylene glycol diacrylate, 1,3-butylene glycol diacrylate, pentaerythritol diacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate.
3. The method according to claim 2, characterized in that: The imidazole ionic liquid is obtained by neutralizing an alkyl imidazole and an acid, the cation of the imidazole ionic liquid includes 1-methylimidazole, and the anion of the imidazole ionic liquid includes at least one of chlorine, tetrafluoroboric acid, hydrogen sulfate, dihydrogen phosphate, trifluoromethanesulfonic acid and trifluoroacetic acid; And / or, the cation of the quaternary ammonium ionic liquid includes at least one of tetraethylammonium, tetrabutylammonium, alkyltriethylammonium and alkyltributylammonium, and the anion of the quaternary ammonium ionic liquid includes at least one of chlorine, bromine, tetrafluoroboric acid, hexafluorophosphoric acid and bistrifluoromethanesulfonimide; And / or, the cation of the quaternary phosphonium ionic liquid includes alkyl tributyl phosphonium, and the anion of the quaternary phosphonium ionic liquid includes at least one of bromine, tetrafluoroboric acid and bistrifluoromethanesulfonimide; And / or, the cation of the pyrrolidine-based ionic liquid includes N-alkylpyrrolidine, and the anion of the pyrrolidine-based ionic liquid includes at least one of bromine, tetrafluoroboric acid, hexafluorophosphoric acid and bistrifluoromethanesulfonimide; And / or, the cation of the piperidine-based ionic liquid includes N-alkylpiperidine, and the anion of the piperidine-based ionic liquid includes at least one of bromine, tetrafluoroboric acid, hexafluorophosphoric acid and bistrifluoromethanesulfonimide.
4. The method according to claim 1 or 2, characterized in that: In step (2), the mass ratio of the modified active component, the polymer monomer and the initiator is (59-98.9): (1-40): (0.1-1); And / or, the boron-containing monomers include at least one of borazine, borosilazane, carborane, boron phenolic acid, cyclic borate, allyloxyborane, allylboronic acid pinacol ester, poly(ethylene glycol) methyl methacrylate containing borane, tetramethoxyboro lithium, boron dipyrromethylethylene, boron difluorohydrazine, azobenzene boron complex, tri(4-vinylbenzene)borane, triarylborane, diarylborane, boron diketonate, tetraphenylborate, tetrakis(4-chloromethyl-2,3,5,6-tetrafluorophenyl)borate lithium, bis(fluoroallyl)malonate lithium borate, bismaleate lithium borate, (bisphenol AF borate) lithium salt, (4,4′-dihydroxydiphenylsulfone borate) lithium salt and bis(allylmalonate) lithium borate; And / or, the sulfate monomer includes at least one of 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane, 4-ethylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane, bis((2,2-dioxo-1,3,2-dioxathiapentane-4-yl)methyl)sulfate, monoethyl sulfate, dibutyl sulfate, diisopropyl sulfate, diethyl sulfate, 1,3-propylene glycol cyclic sulfate, bis(trimethylsilyl) sulfate and S-phenylpyrazine-2-carbon sulfate; and / or, the carbonate monomer comprises at least one of isosorbide bis(alkyl carbonate), trimethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate and butylene carbonate; And / or, the amide monomers include at least one of N-vinylcaprolactam, acrylamide, methacrylamide, N-methylacrylamide, isopropylacrylamide, N-ethylacrylamide, isobutoxymethylacrylamide, N-hydroxymethylacrylamide, diacetoneacrylamide, N-hydroxyethylacrylamide, N-hydroxypropylacrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide; and / or, the ether monomer includes at least one of 1,4-dioxane, ethylene glycol dimethyl ether, glycidyl methyl ether, 1,3-dioxolane, ethylene glycol methyl ether glycidyl ether, 1,3,5-trioxane, diethylene glycol methyl ether glycidyl ether, 1,3-dioxane and 1,4-dioxane; And / or, the fluorine-containing monomer includes at least one of hexafluoropropylene, hexafluorobutyl acrylate, tetrafluoroethylene, hexafluorobutyl methacrylate, vinyl bis(trifluoromethyl) phosphate, trifluoroethyl methacrylate, allyl bis(2,2,2-trifluoroethyl) phosphate, dodecafluoroheptyl methacrylate, allyl bis(trifluoromethyl) phosphate, 2,2,2-trifluoropropylene diphosphate, dodecafluoroheptyl acrylate, nonadecafluoro acrylate, vinyl bis(2,2,2-trifluoroethyl) phosphate and perfluorobutyl ethyl methacrylate; And / or, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovaleronitrile, dimethyl azobisisobutyrate, azoisobutylcyanamide, diisopropyl azodicarboxylate, azobiscyclohexylcarbonitrile, benzoyl peroxide, di(2-ethylhexyl) peroxydicarbonate, tert-butyl perbenzoate, methyl ethyl ketone peroxide, mercaptobenzene, thiolate and alkyl mercaptan.
5. The method according to claim 1 or 2, characterized in that: The polymer monomer includes at least one of a boron-containing monomer and an amide monomer; And / or, an inorganic material is further added to the system of step (2) and mixed to obtain a precursor solution, wherein the inorganic material comprises at least one of an inorganic solid electrolyte and an inorganic ceramic.
6. The method according to claim 5, characterized in that: Based on the total mass of the precursor solution, the mass proportion of the inorganic material is 70% to 95%; And / or, the inorganic solid electrolyte includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a nitride solid electrolyte, a boride solid electrolyte, and a hydride solid electrolyte; And / or, the inorganic ceramic includes at least one of metal oxides, nitrides, carbides, borides and fluorides.
7. A solid electrolyte film, characterized in that: Prepared by the method according to any one of claims 1 to 6.
8. A diaphragm-free solid-state battery, characterized in that: Comprising the solid electrolyte film as claimed in claim 7.
9. A solid-state battery, characterized in that: Comprising the solid electrolyte film as claimed in claim 7.
10. A mechanical device, characterized in that: Including the membrane-free solid-state battery as described in claim 8 or the solid-state battery as described in claim 9.
Citation Information
Cited By
Ultrathin polymer solid electrolyte membrane and preparation method and application thereof
CN120341361A
Polymer composite material, preparation method and application thereof, and lithium ion battery
CN120933460A
Polymer composite material, preparation method and application thereof, and lithium ion battery
CN120933460B